INVESTIGATING PLANT-BASED REMEDIES: THE ROLE OF MEDICINAL PLANTS AS XO INHIBITORS IN GOUT TREATMENT APPROACHES - Anderson , Rachel (Ayden Journal of Agriculture and Allied Studies, 2024)
The escalating demand for pharmaceutical agents sourced from botanical origins has arisen in response to the undesirable repercussions associated with synthetic drugs. This resurgence of interest in traditional medicinal remedies, known for their safety and economical attributes, signifies a pivotal paradigm shift in therapeutic approaches. This research endeavors to assess the viability of medicinal plants as viable alternatives for mitigating gout, an excruciating metabolic disorder ensuing from the accumulation of uric acid within joint vasculature. The pivotal enzyme xanthine oxidase (XO) assumes a critical role in this pathological process, orchestrating the conversion of hypoxanthine to xanthine and culminating in uric acid production. While allopurinol stands as a prominent therapeutic agent restraining gout by thwarting XO activity and impeding uric acid synthesis, the adverse effects attributed to its use have spotlighted the exigency for alternative treatments characterized by marginal side effects. In pursuit of this objective, a cohort of ten medicinal plants was meticulously chosen for comprehensive evaluation, their extracts subjected to rigorous scrutiny for their capacity to inhibit XO function. Employing the precision of spectrophotometry, the percentage of enzymatic inhibition was quantified, unveiling profound insights into the inhibitory potential of the diverse botanical candidates. This inquiry not only substantiates the plausibility of harnessing plant-derived extracts from traditional medicine systems for yielding life-altering pharmaceutical agents but also accentuates their propensity for conferring therapeutic benefits with minimal adversities.